PERAN GURU DAN ORANG TUA TERHADAP STIMULASI KEAKSARAAN ANAK USIA DINI - Isma Ulfadilah; Astuti Darmiyanti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2023)
The research method used is a reference-based literature or library study that is relevant to the topic of the problem and of course varies. The purpose of this study is to determine the role of teachers or parents when stimulating early childhood literacy. Early literacy is one aspect of language development in early childhood. Language and literacy are inextricably linked. The ability of the underlying skills of children begins when the little child feels colors, shapes, understands images, understands pictures, false letters towards the beginning of his name records the letters of his name, notes his considerations despite the fact that the letters are still turbulent or fragmented, pronounces words that most of the time are repeated in a storybook, spelling letters, reading without others, the relationship of sounds to letters, referring to the names of numbers can be indicated by pictures. Methods or methods in literacy, namely: ability in literacy, building reading habits, writing, parental stimulation, implementing learning, creating a language-rich environment, early literacy skills and basic early childhood numeracy, learning media and pre-literacy learning. Without language, a person cannot communicate with others, therefore language plays an important role in allowing people to communicate with each other. This is in line with the belief that various forms of media have a positive effect on the child's thinking and concentration, fine motor skills (eye and hand coordination), patience, language skills, the skill of understanding meaning and knowledge of vocabulary.